2022
DOI: 10.1177/01461672221139072
|View full text |Cite
|
Sign up to set email alerts
|

From Individual Anxiety to Collective Narcissism? Adult Attachment Styles and Different Types of National Commitment

Abstract: National narcissism and national identification, two distinct types of national commitment, differ in terms of their psychological concomitants. Therefore, in the current article, we hypothesized that they would also relate to different adult attachment styles. Namely, we proposed that national narcissism would be positively associated with higher attachment anxiety, while national identification would be associated with lower attachment anxiety and avoidance. These hypotheses were tested in three cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 74 publications
4
20
0
Order By: Relevance
“…Attempting to unravel the interwoven threads of social identity, scholars have turned their attention towards the significance of group attachment for both individual and group‐level processes (Cichocka & Cislak, 2020; Golec de Zavala, 2019; Marchlewska, Górska, et al, 2022). Interestingly, past results demonstrated that individuals may commit to the group they identify with in ways that differ in terms of this relationship's roots, as well as its social consequences (e.g.…”
Section: National Narcissism: Antecedents and Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Attempting to unravel the interwoven threads of social identity, scholars have turned their attention towards the significance of group attachment for both individual and group‐level processes (Cichocka & Cislak, 2020; Golec de Zavala, 2019; Marchlewska, Górska, et al, 2022). Interestingly, past results demonstrated that individuals may commit to the group they identify with in ways that differ in terms of this relationship's roots, as well as its social consequences (e.g.…”
Section: National Narcissism: Antecedents and Outcomesmentioning
confidence: 99%
“…Based on previous theorizing and research, which argued that a weak and threatened ego should be linked to a defensive and hostile, rather than a secure and constructive identity (e.g. Cichocka, 2016; Fromm, 1973; Marchlewska, Górska, et al, 2022), we assumed that individual inability to adaptively cope with life stressors should translate into searching for a strong collective to compensate for individual shortcomings. In contrast, higher ability to cope with stressors in an adaptive way should be linked to lower levels of defensive in‐group identity.…”
Section: National Narcissism: Antecedents and Outcomesmentioning
confidence: 99%
See 3 more Smart Citations